An Elite Bronze Age Double-Horse Burial from Western Ukraine and the Chariot Package Dissemination. (2nd January 2023) - Makarowicz, Przemysław; Ilchyshyn, Vasyl; Pasicka, Edyta; Makowiecki, Daniel
ABSTRACT: The origin and dissemination of paired horse burials and the implications of adopting wheeled vehicle technology on Bronze Age European societies has not been extensively studied. To address this, we present the chronological, artifactual, DNA, contextual, and zooarchaeological analytical results from a Bronze Age double-horse burial in a barrow from Husiatyn, Podolia Upland, western Ukraine. The burial was radiocarbon dated to the 15th century b.c ., and the preserved antler bridle elements are stylistically similar to those from the Carpathian-Danube area. The coat color of the Husiatyn horses was determined from ancient DNA analysis, and their arrangement facing each other, combined with little evidence of lesions on their bones and teeth, suggest they were well treated and probably ridden and/or harnessed to a chariot/cart. We argue that Middle Bronze Age Trzciniec Circle communities northeast of the Carpathians adopted the chariot package as a useful component of their elaborate funerary rituals.